A neuro-psychological study of spiritual characteristics of tyagopanishad / Purushothaman Anantham - Purushothaman , Anantham (2017)
There are no scientific studies attempted on saint Tyagaya‟s musical compositions and its association to the brain mechanism. The research is designed to test the hypothesis that the meditative Sangeetham of Tyagopanishad could produce an unique emotional response in the brain and thus connect to a higher “God Consciousness”. Thus, interpreting that sangeetham as a spiritual practice manifests a „God Form” experience and therefore provides an access to the highest spiritual reality. Special emphasis is placed on how Swami Tyagaya‟s devotion creates the vision of God. The study uses both qualitative and quantitative research methods to analyze and infer the primary and secondary data from reliable literatures, survey and EEG experiments. The qualitative research method endorses the Interpretative Phenomenological Analysis (IPA) methodology for the comprehension of the various literatures. Phenomenological methods are particularly effective at bringing to the fore the experiences of individuals from their own perspectives. The quantitative research method deals with the data of the questionnaire survey and Electroencephalogram (EEG) experiment. The questionnaire survey offers a subjective procedure to rationalize the society‟s view on Saint Tyagaya, sangeetham and spirituality. The intention is to assess their wisdom on devotion, their knowledge on neuropsychological and their perception of God. The Electro-encephalography (EEG) rationalizes scientifically the spiritual characteristics of Swami Tyagaya‟s devotional sangeetham in association with the electrical activity in the brain. It also studies how modern Neuro-Psychology approves this “God- Image” in the brain? The statistical data and the EEG results provide subjective and objective evidences on the values of Tyagaya‟s devotional sangeetham and the brain. The survey findings are derived from four hundred and ten candidates who assisted to reveal their philosophical viewpoint of Swami Tyagaya, sangeetham, brain, God and spirituality. The statistical results show valuable positive correlation between each of them. This survey inference indicates that Swami Tyagaya‟s devotional sangeetham strongly influences the spiritual experience. The EEG experiment was conducted on thirty four volunteers divided into three groups. The Group A volunteers contemplated with Swami Tyagaya‟s sangeethem while Group B and Group C contemplated on devotional songs (not Tyagaya‟s sangeetham). The brain electrical signals of the three groups were compared with one another. The Group A volunteers showed significant increase of 100% Alpha activity and 83% Theta activity when compared with the control Group B and Group C. The Group A finding is inspiring and educative. The EEG results clarify the pattern and nature of devotion and identify the long environmental influence that perhaps creates the state of relaxation of the brain to visualize “God”. The research successfully proves that the meditative nature of Swami Tyagaya‟s devotional sangeetham develops the experience of God in the human brain. This spiritual association can engage the society to activate compassion, love and tolerance. The conclusion is that the vision of God is a manifestation in the brain by a long term practice of devotional sangeetham. It appears that spirituality may be natural as described by Dr. Andrew Newberg, Swami Tyagaya and Swami Yatiswarananda. The research on sangeetham as a tool can be incorporated into schools for psychotherapy and into hospitals for health therapy.